Islam and Rationality. The Impact of al-Ghazālī. Papers on the occasion of his 900th anniversary - Tamer, Georges (Brill, 2015)
This volume offers an account of Abū Ḥāmid al-Ghazālī (d. 505/1111) as a rational theologian who created a symbiosis of philosophy and theology and infused rationality into Sufism. The majority of the papers herein deal with important topics of al-Ghazālī’s work, which demonstrate his rational treatment of the Qurʾān and major subjects of Islamic theology and everyday life of Muslims. Some other contributions address al-Ghazālī’s sources and how his intellectual endeavors were later received by scholars who had the same concern of reconciling religion and rationality within Islam, Christianity and Judaism.
Keywords: Islamic Philosophy; Abu Hamid al-Ghazali